PENINGKATAN KESADARAN ETIKA DAN BERPIKIR KRITIS MELALUI EDUKASI PENGGUNAAN GENERATIVE AI - Nabila Putri; Allya Putri Erly Perdani; Nabilah Maymoenah; Muhammad Faiz Hidayah; Muhammad Ardan; Darmeli Nasution (Jurnal Masyarakat Indonesia (Jumas), 2025)
The rapid development of generative artificial intelligence (AI) has significantly influenced various aspects of daily life, including the field of education. While generative AI offers substantial benefits in enhancing creativity, learning efficiency, and access to information, its uncontrolled and unethical use may negatively affect users’ critical thinking abilities, academic integrity, and moral responsibility. This community service activity aims to increase awareness of ethical considerations and critical thinking skills through educational programs on the responsible use of generative AI. The implementation methods include educational seminars, interactive discussions, and practical demonstrations on the proper, ethical, and critical use of generative AI tools in learning activities. The program targets community members and learners, emphasizing the importance of understanding both the advantages and potential risks of generative AI. The results of the activity indicate an improvement in participants’ understanding of ethical AI use, increased awareness of the limitations of generative AI, and enhanced critical thinking in evaluating AI-generated information. This activity is expected to contribute to the development of responsible, ethical, and reflective AI users, thereby supporting the improvement of learning quality in the digital era.